Melting temperature of iron at high pressure: statistical moment method approach - Thi Hai, Tran (VNU Journal of Science: Mathematics - Physics; Vol 33 No 3DO - 10.25073/2588-1124/vnumap.4092, 2017)
The pressure effects on melting temperatures of iron have been studied based on the combination of the modified Lindemann criterion with statistical moment method in quantum statistical mechanics. Numerical calculations have been performed up to pressure 150 GPa. Our results are in good and reasonable agreements with available experimental data. This approach gives us a relatively simple method for qualitatively calculating high-pressure melting temperature. Moreover, it can be used to verify future experimental and theoretical works. This research proposes the potential of the combination of statistical moment method and the modified Lindemann criterion on predicting high-pressure melting of materials.